2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28092
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Evidence-Based Pedagogies in STEM Education

Abstract: little understood question that has motivated her program of research is: How can we effectively and efficiently promote cyberlearning in complex knowledge domains such as STEM (science, technology, engineering and mathematics)? Towards this direction, she (1) investigates the development of higher-order thinking and complex problem-solving competencies following a comprehensive framework that includes cognition, metacognition, cognitive regulation, motivation, emotion, and epistemic beliefs; (2) develops inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It is crucial to provide early guidance to teachers about the peer-review process during their undergraduate education, enabling them to confidently submit their findings when conducting inquiries in teaching. Teachers who present their findings from teaching inquiries at academic conferences or publish them in peer-reviewed journals are more inclined to adopt student-centered approaches than teachers who do not share their findings or do not actively participate in the peer-review process (Curtis et al, 2013; McKenna et al, 2009; Yalvac et al, 2017). Formal engagement in the peer-review process is critical for teachers to fully appreciate the essence of student-centered teaching approaches.…”
Section: Inquiry In Scientific Enterprisementioning
confidence: 99%
“…It is crucial to provide early guidance to teachers about the peer-review process during their undergraduate education, enabling them to confidently submit their findings when conducting inquiries in teaching. Teachers who present their findings from teaching inquiries at academic conferences or publish them in peer-reviewed journals are more inclined to adopt student-centered approaches than teachers who do not share their findings or do not actively participate in the peer-review process (Curtis et al, 2013; McKenna et al, 2009; Yalvac et al, 2017). Formal engagement in the peer-review process is critical for teachers to fully appreciate the essence of student-centered teaching approaches.…”
Section: Inquiry In Scientific Enterprisementioning
confidence: 99%
“…Evidence-based pedagogies are often student-centered and learner-oriented [3], [9], [10]. Bransford, Brown, and Cocking (2000) reported that an effective learning environment includes the following four characteristics: (a) knowledge-centeredness, (b) learner-centeredness, (c) assessment-centeredness, and (d) community-centeredness [3].…”
Section: Evidence-based Pedagogiesmentioning
confidence: 99%